Answer:
The point slope equation be
.
Explanation:
The point slope equation of the line is given by .
![(y-y_(1))=m (x-x_(1))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xxoit2ik40r5uvrd4pibbraj9mmp1n3cly.png)
Where m is the slope .
![m =(y_(2)-y_(1))/(x_(2)-x_(1))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/an1n09vxg9txswl28zgzc1exryaxj01hfi.png)
![m =\frac{1-(-3){12-4}]()
![m =(4)/(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/uucdlakan5gu16tw3kq8jw3gkh7ow26pqd.png)
![m = (1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mtcchyrun624rx2vmwj4ms7xhop125ab7f.png)
As given
The point-slope form of the equation of the line that passes through (4, -3) and (12, 1) is
.
Putting the values in the point slope equation .
![(y-(-3))=(1)/(2)(x-4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hxdqlrrk4m459jwpo9aqszdg02m618ynf6.png)
![2* (y+3)=x-4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3tezuuw7f4xa4yy2t3jq8khqyqh75ny9hx.png)
2y + 6 = x - 4
2y = x - 4 - 6
2y = x -10
![y = (1x)/(2)-(10)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fhgxdfkke45vo3xqjv610x85oz106rg5qr.png)
![y = (1x)/(2)-5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fauqhhwil7ech4tv3ldjs2b4adnx2686fi.png)
Therefore the point slope equation be
.